ОБРАЗОВАТЕЛЬНО-ВОСПИТАТЕЛЬНЫЕ ПРАКТИКИ ТЬЮТОРСТВА ЗАРУБЕЖНЫХ ВУЗОВ - Кулниязов, Т.У. (SCIENCE and SOCIETY, 2022)
This article deals with the tutoring system in Europe, it reveals the definition of the concept of "tutorship", the content and structure of tutoring work, the features of the tutoring system, the practice of the tutoring system abroad.